Diversity and distribution of ferns and clubmosses in the eastern canyons of Isalo National Park, Madagascar - Rivoharifara Randrianarimanana; France Rakotondrainibe; Elodie Boucheron-Dubuisson; Lovanomenjanahary Marline; Mijoro Rakotoarinivo; Catherine Reeb (Plant Ecology and Evolution, 2024)
Background and aims – In contrast to the flowering plants, the pteridophyte flora of Madagascar is still understudied. While several studies have been published on the eastern and central parts of the island, there are currently few works dedicated to the pteridophytes of southwestern Madagascar. The aim of this work is to increase the knowledge of the pteridophyte flora of the Isalo massif in southwestern Madagascar. It presents a checklist of Isalo’s pteridophytes and an analysis of the diversity and distribution patterns of pteridophyte communities across ecological gradients in the eastern canyons of Isalo. Material and methods – Eighty plots were placed in six canyons. In each plot, pteridophyte species abundance was inventoried, as well as several ecological and geomorphological variables. A census in the field and observations on specimens in herbaria were carried to make a checklist of all the pteridophyte species known for Isalo. Statistical analysis was carried out to understand the pteridophyte diversity and distribution patterns in the Isalo’s canyons: (1) exploratory analysis (FAMD and HCPC) highlights the general patterns of ecological gradients, (2) a rarefaction curve was used to compare species diversity, and (3) co-inertia analysis investigated the relationship between ecological gradient and pteridophyte communities. Key results – In total, 60 species of ferns and lycophytes have been recorded in the massif, including ten endemic species to Madagascar and 11 species reported for the first time in the Isalo massif. Species diversity is especially high in the northern canyons (Anjofo, Andramanero, Antsifotra) in contrast to the middle (Maki and Rats) and southern (Namaza) canyons. Fern distribution patterns were correlated to a combination of environmental factors, highlighting species-specific ecological preferences.